Metode Pendekatan Top-down dan Bottom-up: Strategi Marketing Penetapan Harga di Pelayanan Kesehatan - Muchtar, Muchtar; Sulistiadi, Wahyu (UI Scholars Hub, 2018)
The marketing mix consists of product, price, place and promotion. Pricing in health services is an important mix that can be done through the top-down and bottom-up approach. The purpose of this paper is to review the differences between the top-down and bottom-up approaches to pricing health services. Method: This literature review is conducted in December 2018. Research related to the top-down and bottom-up approaches to pricing health services is sought by using valid keywords, including top down approaches, bottom-up approaches and costing through PubMed, Science Direct and EBSCO. Results & Discussion: A total of 10 papers were selected for the literature review. The result is that a top-down approach is carried out if you want to see large product-scale costs and estimate costs in the longer term, a bottom-up approach is done if we want to assess how much variation in costs is needed in production activities. The top-down approach will produce cost variants that are more evenly distributed and do not have many variants, while bottom-up will produce cost variants that are individual and very complex. Conclusion: By understanding the method of top-down and bottom-up approach in calculating costs, the administrator has a strong basis in pricing, calculation of profit margins and marketing cost budgeting, and marketing strategies that can be done to increase public access to health services, so that income diversification can be done and hospitals can survive in the JKN era.